Analisis Python Penggunaan Musik Sebagai Pengobatan Gangguan Mental - Raja Adi Pranata; Jeremy Reynald; Farhan Armandy Rasyid; Joevan Alezka; Muhammad Indra Ferdinand; Tubagus Zakki Ibrahim Ahmad; Rizki Budiman; Rahmi Yulia Ningsih (Lembaga Pengembangan Kinerja Dosen, 2023)
Music has become an important part of mental healing efforta. This is because music can reduce anxiety, such as symptoms of depression, anxiety, fear and have a positive effect on mood. However, research that describes statistically and explains visually is still rarely done. Therefore, this study aims to describe statistically and visualize the effectiveness of music as a healing of mental disorders. Through the literature study method, namely the search for references related to mental diseases and music, and pyton analysis, namely to conduct statistical data analysis and visualize data. The results explained that sufferers of mental disorders who listen to music are anxiety, depression, insomnia, OCD, the average age of listening to music that is affected by mental disorders of 14 years to 20 years as many as 300 people, on average per day listening to music for three hours a day as many as 175 as many as 175 People, the effectiveness of healing listening to music as many as 548 people from 736 people or in a percentage of 74.5% of the success rate of music in curing mental illness. This study proves that mental disorders can be cured by listening to music, especially music with rock and pop genres. This research contributes to the knowledge of listening to music into an alternative to healing mental disorders.Therefore future research is necessary to study in other mental disease disorders, not limited to patients with anxiety, Isomania, depression, OCD.